Recent Developments in Nanomaterial-based Shear-sensitive Drug Delivery Systems - Wang, Yi (Adv Healthc Mater, 2021)
Nanomaterial-based drug delivery systems (DDSs) increase the efficacy of various therapeutics, and shear stress has been shown to be a robust modulator of payload release. In the past few decades, a deeper understanding has been gained on the effects of flow in the body and its alteration in pathological microenvironments. More recently, shear-responsive nanomaterial DDSs have been developed. Here we review studies on this subject mainly from the last decade, focusing on innovations of the material design and mechanisms of the shear response. The two most popular shear-controlled drug carriers distinguished by different release mechanisms, i.e. shear-deformable nanoparticles (NPs) and shear-dissociated nanoparticle aggregates (NPAs) are surveyed. The influence of material structures on their properties such as drug loading, circulation time and shear sensitivity are discussed. We further inspect the drug development stages, therapeutic effects, limitations and potential of these DDSs. The reviewed research emphasizes the advantages and significance of nanomaterial-based shear-sensitive DDSs in the field of targeted drug delivery. We also believe that efforts to rationally design nanomaterial DDSs responsive to shear may prompt a new class of diagnostics and therapeutics for signaling and rectifying pathological flows in the body.